2019
DOI: 10.1007/s11096-019-00907-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of pharmacists’ interventions to support medicines optimisation in patients with visual impairment

Abstract: Background People with visual impairment often report poorer health and encounter many challenges when using medicines. Pharmacists can play a significant role in optimising medicines use for these patients. However, little is known about pharmacists’ current practices when providing services to this population nor the impact of such services, if any, on medicines optimisation-related outcomes. Aim of the review This systematic review aims to identify the types, and assess the effectiveness of, interventions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Most publications were from KSA and Jordan, covering a lot of topics from safe pharmacy practices to topics like role of pharmacists in helping visually impaired persons. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Most publications were from KSA and Jordan, covering a lot of topics from safe pharmacy practices to topics like role of pharmacists in helping visually impaired persons. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…There are still relatively few reviews in the field of PS, be they systematic, narrative, scoping, or qualitative. This may be because the growth in research in this area is only recent and there is therefore an unmet need to bring together enough references on the same topic to ensure a robust review [40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews of the pharmaceutical care of people with sensory impairments identified no studies of interventions that sought to improve this care [28,48]. However, opportunities to enhance both the professional support, (e.g., communication skills) and the organisational framework (e.g., engagement of sign language interpreters and implementation of tailored dispensing and packaging interventions) so as to support people with sensory impairments have been documented.…”
Section: What Are the Opportunities To Enhance Equity In Medication O...mentioning
confidence: 99%